2017
DOI: 10.1002/ejoc.201601524
|View full text |Cite
|
Sign up to set email alerts
|

Schreiner's Thiourea Promoted [2+2] Cycloaddition of Captodative Azetidinones and Nitroolefins

Abstract: Strained, captodative benzylideneazetidinones were demonstrated to function as potent reaction partners in thermal [2+2] cycloadditions with nitro alkenes. The relief of strain during the cycloaddition could be leveraged to secure kinetic and thermodynamic stability for the aminonitrocyclobutane ring. Accordingly, this mild and robust procedure could be used to simplify the synthesis of azaspiro[3.3]heptanes, a motif that serves as a rigid piperidine bioisostere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…However, we found that under identical conditions, only the competing Passerini product was formed. We assumed that the required imine intermediate formation was hampered and the process halted at the hemiaminal stage due to the ring strain [51,52] . To facilitate the imine formation from the hemiaminal and activate the imine intermediate, [53] we probed various polar and protic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that under identical conditions, only the competing Passerini product was formed. We assumed that the required imine intermediate formation was hampered and the process halted at the hemiaminal stage due to the ring strain [51,52] . To facilitate the imine formation from the hemiaminal and activate the imine intermediate, [53] we probed various polar and protic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…To study the performance of organocatalysts and Hbonding effects on the reaction, we investigated the reactions between 1a and 2a catalyzed by 3b, 3c, 3d, and 3e (denoted as reactions [11][12][13][14], respectively. Catalyst 3b was obtained by phenyl replacing 3,5-(CF 3 ) 2 -Ph of 3a.…”
Section: Preliminary Investigation For the H-bonding Effectsmentioning
confidence: 99%
“…In recent years, organocatalytic [2 + 2] cycloadditions have received widespread attentions since they are low cost and environmentally friendly . In particular, organic amines employed as catalysts for [2 + 2] cycloadditions have led to a rising interest.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that formation of cyclobutane derivatives from enamines and electron-withdrawing group (EWG)-substituted alkenes has been reported since the 1960s (for representative instances see Figure 1), 2 most papers seldom mention the role or involvement of cyclobutanes as intermediates. The more recent works of the groups of Seebach, Hayashi, Blackmond, Pihko, and Papai are the exception.…”
Section: Introductionmentioning
confidence: 99%